Pendampingan Investasi Saham Syariah pada ASN di Lingkungan Satkordikcam Jepara - Arumsari, Nurul Rizka; Ermawati, Nanik; Zainuri, Muhammad (LPPM UNS, 2022)
Nowadays, everyone's needs and wants are huge. Needs and wants become difficult to distinguish because of the changing times that are increasingly advanced. Lifestyle makes people have a lot of demands. To fulfill this, it is not enough to just rely on a monthly salary. Therefore, we must look for ways to be able to utilize the finances we have to meet our needs and desires. One way that can be taken is by investing.Along with the mandate of service, it is deemed necessary to convey knowledge transfer to organizations that play an important role in the community. Among them are the Department of Education, Youth and Sports, Jepara sub-district, Jepara district. It is considered important because there is still limited knowledge and stigma in the community about investing in sharia shares in the capital market. Sharia stock investment material in the capital market will be very helpful for people who will invest in sharia in the capital market and can become an investor.The result of service activities for ASN in the Jepara Satkordikcam environment is that ASN understands capital market theory, the basics of Islamic capital market, is able to practice open accounts through MNC Sekuritas, and is able to understand the management of family financial management